'Addicted to being cool': occasional smoking in a western context of tobacco denormalization. (3rd September 2017) - Scheffels, Janne; Tokle, Rikke
Abstract: Background: Although the prevalence of daily smokers are decreasing and there are signs of increasing stigma attached to smoking, occasional smoking rates have remained surprisingly stable. The increasing proportion of smokers who do not smoke daily emphasize the importance of understanding the reasoning behind this pattern of smoking. We explored how young adult occasional smokers in Norway viewed and defined their smoking and how they managed their smoker identities in a western context of tobacco denormalization. Methods: 17 young adult occasional smokers (aged 24–31) were interviewed in-depth about smoking practices, attitudes towards smoking and occasional smoking in relation to self-presentation and social image. Findings: The occasional smokers told detailed stories of how, when and in what situations they smoked, and in this, positioned their smoking as controlled and different from stigmatized daily smoking. Drinking situations were the most important context for occasional smoking, and they described occasional smoking and drinking alcohol in similar ways: as letting control go in a controlled way. Occasional smoking was positioned as a symbol of individualism and of transgression. Conclusion: Strategies aiming at repositioning occasional smoking as uncool may be relevant to motivate occasional smokers to quit. Because alcohol plays such an important role in facilitating occasional smoking, extending smoke-free areas outside bars could also be a way to reduce occasional smoking.